Tailoring the microstructure and mechanical properties of H13 steel by controlling the pre-precipitation of VC carbides from austenite - Xiaofang Wang; Chuanwei Li; Zhifeng Zhang; Xiaoli Zhao; Daming Tong; Guanghua Yan; Lizhan Han; Jianfeng Gu (Journal of Materials Research and Technology)
Carbides play an important role in influencing the phase transformation and mechanical properties of steels. In this work, the microstructure of H13 steel is tailored by controlling the pre-precipitation of VC carbides at 950 °C to obtain excellent mechanical properties. It is revealed that the pre-precipitation of VC carbides decreases the carbon content of austenite, thus resulting in a high temperature of Ms. With the increasing amount of pre-precipitated VC carbide, martensite transformation is firstly accelerated by the enhanced transformation driving force, and then decelerated due to the hindering effect of VC particles on the growth of martensite laths. The improvement in strength, ductility and toughness of quenched H13 steel can be attributed to the pre-precipitated VC carbides and the refined martensite blocks. The tempered H13 steel with pre-precipitated VC carbides also exhibits excellent ductility and toughness. It can be concluded that controlling the pre-precipitation of VC carbides from austenite is an effective method to tailor the mechanical properties of H13 steel.